Um problema de corte de estoque multiobjetivo - Salles-Neto, Luis Leduíno; Araujo, Silvio Alexandre de [UNESP]; Golfeto, Rodrigo Rabello (My University, 2014)
In this paper we deal with the one-dimensional integer cutting stock problem, which consists of cutting a set of available objects in stock in order to produce ordered smaller items in such a way as to optimize a given objective function, which in this paper is composed of three different objectives: minimization of the number of objects to be cut (raw material), minimization of the number of different cutting patterns (setup time), minimization of the number of saw cycles (optimization of the saw productivity). For solving this complex problem we adopt a multiobjective approach in which we adapt, for the problem studied, a symbiotic genetic algorithm proposed in the literature. Some theoretical and computational results are presented.

Neste trabalho, estuda-se o problema de corte de estoque unidimensional que consiste em cortar um conjunto de objetos disponíveis em estoques, para produzir uma demanda de itens menores de forma a otimizar uma determinada função objetivo que, neste trabalho é composta por três objetivos distintos: minimização do número de objetos processados (matéria-prima), minimização do número de diferentes padrões de corte (tempo de preparação da máquina), minimização do número de ciclos de serra (otimização da produtividade da serra). Para a resolução deste problema complexo foi adaptado um algoritmo genético simbiótico proposto na literatura. Alguns resultados teóricos e computacionais são apresentados.
Keywords: Problema de corte de estoque; Otimização multiobjetivo; Algoritimo genético simbiótico; Cutting stock problem; Multiobjective optimization; Genetic symbiotic algorithm